2012
DOI: 10.1021/ic202124x
|View full text |Cite
|
Sign up to set email alerts
|

27Al and 29Si Solid-State NMR Characterization of Calcium-Aluminosilicate-Hydrate

Abstract: Calcium silicate hydrate (C-S-H) is the main constituent of hydrated cement paste and determines its cohesive properties. Because of the environmental impact of cement industry, it is more and more common to replace a part of the clinker in cement by secondary cementitious materials (SCMs). These SCMs are generally alumina-rich and as a consequence some aluminum is incorporated into the C-S-H. This may have consequences on the cohesion and durability of the material, and it is thus of importance to know the am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
149
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 255 publications
(172 citation statements)
references
References 36 publications
22
149
1
Order By: Relevance
“…Sun et al [11] suggested that Al(V) and Al(VI) could compensate the negative charge introduced by the replacement of Si(+ IV) by Al(+ III) in the silica chain. However, the amount of Al(V) and Al(VI) does not correlate with the amount of Al(IV) in the silica chains [10,13].…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations
“…Sun et al [11] suggested that Al(V) and Al(VI) could compensate the negative charge introduced by the replacement of Si(+ IV) by Al(+ III) in the silica chain. However, the amount of Al(V) and Al(VI) does not correlate with the amount of Al(IV) in the silica chains [10,13].…”
Section: Introductionmentioning
confidence: 90%
“…The substitution of aluminium occurs primarily as tetrahedrally coordinated Al(IV) in the bridging position (Q 2 b ) [9][10][11][12], as indicated in Fig. 1.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The spectra were subjected to the deconvolution in a qualitative calculation [19][20][21][22]. From the NMR data of the specimen 14 days after prepared, there were three types of Na + inside the specimen.…”
Section: The Influence Of Ph On Structural Change As Determined By Nmrmentioning
confidence: 99%